2010
DOI: 10.17221/2447-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in portuguese native Vitis vinifera L. ssp. vinifera and ssp. sylvestris

Abstract: To assess the different origins of Portuguese grapevine varieties, we used six nuclear and four chloroplastidal microsatellites as molecular markers, in order to compare the genetic structure of native wild-vines with native grapevine varieties. Both native subspecies have a great diversity, and a high interrelationship across the six nuclear microsatellites. Although identical numbers of alleles were found in each population, their distribution was different in the <I>vinifera </I>and <I>syl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The results of the genetic analysis showed that La Minilla still harbors a number of wild grapevine accessions with low levels of heterozygosity (He). Similar result has been observed in wild grapevine populations analyzed in Morocco, Sardinia, Portugal, France or Italy (Di Vecchi-Staraz et al, 2009;Cunha et al, 2010;Zecca et al, 2010;Zinelabidine et al, 2010). However, we have detected that the observed heterozygosity (Ho) was not significantly lower (p≤0.05) than expected heterozygosity (He) in La Minilla populations, in parallel with the estimation of F values close to zero (Table 2).…”
Section: Discussionsupporting
confidence: 82%
“…The results of the genetic analysis showed that La Minilla still harbors a number of wild grapevine accessions with low levels of heterozygosity (He). Similar result has been observed in wild grapevine populations analyzed in Morocco, Sardinia, Portugal, France or Italy (Di Vecchi-Staraz et al, 2009;Cunha et al, 2010;Zecca et al, 2010;Zinelabidine et al, 2010). However, we have detected that the observed heterozygosity (Ho) was not significantly lower (p≤0.05) than expected heterozygosity (He) in La Minilla populations, in parallel with the estimation of F values close to zero (Table 2).…”
Section: Discussionsupporting
confidence: 82%
“…sylvestris . Specimens of the latter can still be found, however, growing in Greece, France, Romania (Walker 1985) and the Spanish regions of Asturias, La Rioja, Extremadura and Andalusia (Föex 1891, Rivera and Walker 1989, Ocete et al 1999, Rivas‐Martínez et al 2002, Arroyo‐García et al 2006, Cunha et al 2007, 2010, Arroyo‐García and Revilla 2013).…”
Section: Introductionmentioning
confidence: 99%
“…According to the first kind, grapevines were introduced via commercial activity and through the movement of populations across the Mediterranean area during protohistoric times (Negrul 1938, Levadoux 1956, Olmo 1996, McGovern 2004, This et al 2006). In contrast, indigenist theories (currently the most widely accepted) suggest cultivated vines appeared independently in different parts of the Mediterranean and Middle East, with the wild plants of different areas being domesticated (Levadoux 1956, Stevenson 1985, Lacombe et al 2003, Laguna 2003, Arroyo‐García et al 2006, This et al 2006, Cunha et al 2010, De Andrés et al 2012, Arroyo‐García and Revilla 2013). Certainly, however, they could have spread out from these different points of origin.…”
Section: Introductionmentioning
confidence: 99%